Simultaneous Determination of Copper, Lead, and Cadmium Ions at a Mo6S9-xIx Nanowires Modified Glassy Carbon Electrode Using Differential Pulse Anodic Stripping Voltammetry. (1st February 2015) - Lin, Hong; Li, Meixian; Mihailovič, Dragan
Graphical abstract: Highlights: An electrochemical sensor based on Mo6 S9-x Ix nanowires was constructed. Mo6 S9-x Ix nanowires can amplify electrochemical responses of heavy metal ions. Mo6 S9-x Ix nanowires can promote electron transfer. Mo6 S9-x Ix nanowires can accumulate metal ions due to large surface area. The preparation of the sensor is simple, short-time and it does not require a special apparatus. ABSTRACT: A novel electrochemical sensor based on a new kind of nanomaterials Mo6 S9-x Ix nanowires modified glassy carbon electrode (GCE) was constructed for simultaneous determination of cadmium(II), lead(II) and copper(II) using differential pulse anodic stripping voltammetry (DPASV). Various experimental parameters such as the modified amount, pH, deposition time and deposition potential were optimized. Under the optimal conditions, the stripping peak currents increase linearly with increasing concentrations of Cd(II), Pb(II) and Cu(II) ions in the ranges of 0.5∼150 μg · L −1, 1.5∼450 μg · L −1 and 0.8～240 μg · μg·L −1, 1.5∼450 μg·L −1 and 0.8∼240 μg·L −1, respectively. And the limits of detection (S/N = 3) are estimated to be 0.10 μg · L −1 for Cd (II), 0.45 μg·L −1 for Pb(II) and 0.20 μg·L −1 for Cu(II), which are two orders of magnitude lower than those obtained at the unmodified electrodes. Most importantly, the sensor has been successfully applied to the determination of trace metal ions in the tap water samples. This developed electrochemical sensor exhibits high sensitivity, good stability and reproducibility.